If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10x(x+2)=5(x+8)
We move all terms to the left:
10x(x+2)-(5(x+8))=0
We multiply parentheses
10x^2+20x-(5(x+8))=0
We calculate terms in parentheses: -(5(x+8)), so:We get rid of parentheses
5(x+8)
We multiply parentheses
5x+40
Back to the equation:
-(5x+40)
10x^2+20x-5x-40=0
We add all the numbers together, and all the variables
10x^2+15x-40=0
a = 10; b = 15; c = -40;
Δ = b2-4ac
Δ = 152-4·10·(-40)
Δ = 1825
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{1825}=\sqrt{25*73}=\sqrt{25}*\sqrt{73}=5\sqrt{73}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(15)-5\sqrt{73}}{2*10}=\frac{-15-5\sqrt{73}}{20} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(15)+5\sqrt{73}}{2*10}=\frac{-15+5\sqrt{73}}{20} $
| 3x-1/7=1/2x-3/2 | | .05x+.15(70)=24.5 | | 6(2w-3=6w | | 3=1/4(m-4)+1/4m | | 4c^2+13c+42=0 | | 3+5n=5(+2)-7 | | 9+3x+2-2x=67 | | 10s+67=-5-2s | | 14+4=-2(2x-9) | | 30^2+4p+10=0 | | G+2g-2g=15 | | 5(x+20)=700 | | -27=3/4t | | 144=17x+1+18x+3 | | 4-n+3=n*2-9 | | 1/3x-2=-4 | | 9(x-10)-7=50 | | 5x-4=31-2x | | 3(2x+9)=-47+56 | | 3p^2+4p+10=0 | | -.875x=24 | | 8j-4j+2j+4j-7j=12 | | 240.00+x(0.15)=340.50 | | 5h+6h=77 | | 11=-29k | | -4=11=x | | p^2=17p-60 | | -15+7p=41 | | 2y=18-7y | | -1x+88=133+-6x | | m/6-10=-12 | | 3w-5=2w+w |